Analisis Strategi Pemasaran Kopi Benteng Alla di Kabupaten Enrekang - Rista Astari Rusdin (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2021)
Strategy Marketing Analysis of Benteng Alla Arabica Coffee in Kabupaten Enrekang: A case study of Benteng Alla Utara Farmers Cooperation (KTBAU) Kecamatan Baroko, Kabupaten Enrekang. This study aimed to determine the relevant marketing strategy applied that used by Benteng Alla Utara Farmers Cooperation (KTBAU) to enhance the marketing performance of Benteng Alla Arabica Coffee. This study use a case study method (observational case studied) with qualitative and quantitative approaches. Data is processed by determining strategic factors then used in the input stage (IFE and EFE Matrix), followed by an analysis phase using SWOT/ TOWS Matrix, IE Matrix, and Grand Strategy. The results are proccessed using the QSPM Matrix to obtain the right alternative strategies for KTBAU. The results showed that the Total Attractives Score (TAS) based on the QSPM matrix found that the alternative that corresponds to the current conditions is the highest market penetration rate of 5,557 compared to the alternative product development strategy with a score of 5,556 and alternative market development with a score of 5,553.